ANALISIS SIMULASI KEKUATAN DAN PEMBUATAN RANGKA KENDARAAN SEPEDA MOTOR LISTRIK - Ricky Setiawan; Didik Sugiyanto; Asyari Dariyus (Jurnal Konversi Energi dan Manufaktur, 2023)
The development of the automotive industry, especially my vehicle transportation, has changed from a fuel motor to an electric motor vehicle. The purpose of writing is to get results from the simulation of frame design and power on an electric motorcycle. The simulation result from the design where the material used is low carbon steel that the frame of an electric motorcycle with a rider weight of 170 kg is safe based on the "machine element" book on the dynamic load safety factor, which is determined from 2.0-3.0 For static loads 1.25-2.0 and shocks 3-5 this frame construction includes dynamic loads, displacement resulting from the stress analysis of the electric motorcycle frame receiving a load of 1700 N which is assumed to be the weight of the rider. Based on the simulation results, the maximum displacement is 0.2118 mm, and the von Mises stress generated by the stress analysis of the electric motorcycle frame receives a load of 1700 N, which is assumed to be the weight of the rider. Based on the simulation results, the maximum von Mises is 101.3 MPa. The von mises voltage. This electric motorcycle uses a 48 V BLDC brushless motor, 1500 W, 550 rpm, and uses a 58 V and 24 Ah lithium-ion battery.